The Influence of Severe Plastic Deformation and Low-Temperature Annealing on the Behavior of C11000 Copper under Sliding Friction without Lubricant - Filippov, A. V. (Journal of friction and wear, 2025)
M1 Copper samples with different structural states were obtained by equal-channel angular pressing and subsequent annealing. The structure of the samples before and after sliding friction tests was studied by transmission electron microscopy and metallography. The mechanical characteristics of the samples were determined during tensile tests and nanoindentation. During friction according to the ball-on-disk scheme, the friction coefficient, vibration, and acoustic emission were recorded to identify the features of the influence of the structural state of the material on the friction dynamics. Confocal laser scanning microscopy was used to assess wear. It was found that an increase in the number of equal channel angle pressing (ECAP) passes and annealing have an insignificant, no more than 8%, effect on the sliding friction coefficient in the steel–copper pair. It is shown that an increase in the number of ECAP passes can reduce the wear of M1 copper by 26–93%. After annealing at a temperature of 200°C, wear is additionally reduced by 5–8%, compared to samples without annealing. Annealing at 300°C leads to an increase in wear by 37–65%, compared to samples without annealing. Low plasticity and high hardness of the material in a highly deformed state lead to the formation of a thick surface layer consisting of a mixture of oxidized wear particles, copper oxides, and fragments of the destroyed friction surface. Annealing at temperatures of 200 and 300°C contributes to less pronounced destruction of the surface of the samples, as well as oxidation and mixing with wear particles in a thinner surface layer. The results indicate a significant effect of the structural state on both the mechanical properties and the features of the sliding friction and wear process of M1 copper.